2006
DOI: 10.1002/ijc.22026
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of telomere length regulating factors TRF1, TRF2 and TIN2 in patients with adult T‐cell leukemia

Abstract: Here, we report that freshly isolated unstimulated adult T-cell leukemia (ATL) cells present high telomerase activity compared to asymptomatic carriers or normal donors. In spite of this high telomerase activity, ATL cells retained shorter telomeres compared to those of uninfected cells isolated from the same patients. Because the safeguarding of telomere length is critical to the unlimited proliferation of tumor cells, we investigated the underlying mechanism for short telomere maintenance in ATL cells. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 49 publications
2
62
0
3
Order By: Relevance
“…Dysfunctional telomeres may arise either from critically short telomeres or by disruption of the shelterin complex [28]. In some hematologic malignancies, altered expression of shelterin proteins might disrupt the telomere structure, contributing to malignant transformation [13,[28][29][30][31]. Particularly in MCL, to our knowledge, there is only one report on the expression levels of TRF1, TRF2, TNKS, and PIF1 in a limited number of patients (7-8 cases) [30] and no differences in gene expression were found in comparison to lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional telomeres may arise either from critically short telomeres or by disruption of the shelterin complex [28]. In some hematologic malignancies, altered expression of shelterin proteins might disrupt the telomere structure, contributing to malignant transformation [13,[28][29][30][31]. Particularly in MCL, to our knowledge, there is only one report on the expression levels of TRF1, TRF2, TNKS, and PIF1 in a limited number of patients (7-8 cases) [30] and no differences in gene expression were found in comparison to lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-I has evolved multiple strategies to prevent apoptosis and to extend the life span of infected cells (23)(24)(25)(26)(27). In turn, this allows accumulation of genetic mutations and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…A year later, Bellon et al (2006) reported that TL measured by Q-FISH was shortened in adult T-cell leukaemia/lymphoma. They further showed that TA was significantly increased though they postulated that this increase did not result in longer TL due to overexpression of TERF1, TERF2 and POT1, shelterin proteins that regulate the recruitment of telomerase at the terminus (Bellon et al, 2006).…”
Section: T Cell Malignanciesmentioning
confidence: 99%